Technical Efficiency of State-Owned Sugarcane Production in East Java - Muhammad Taufik Yusuf; Jamhari Jamhari; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2020)
This study aims to (1) identify the factors that influence the production of plant cane and ratoon cane, (2) determine the level of production efficiency of plant cane, ratoon cane, and poll, and (3) identify the factors that influence the inefficiency of plant cane and ratoon cane production. The data used was secondary data sourced from the production data for the 2017-2018 planting season with some inputs: land area, fertilizers, herbicides, labor, age of plants harvested and data of land types. From the analysis, it was revealed that (1) factors influencing the increase of plant cane production were land area, ZA fertilizer, harvest labor, and types of fields. Meanwhile, the influential factors impacting the increase of ratoon cane were land area, SP36 fertilizer, ametryn herbicide, harvest labor, type of fields, and HGU land type while estate labor, mechanization, and dummy varieties affect decreasing on it, (2) sugarcane farming was technically efficient (3) factors affecting the inefficiency for plant cane are formal education and rank levels of plant officer. However the coefficient of the formal education variable was negative and the rank level coefficient was positive. A higher level of education will increase production, but a higher rank level of plant officer will decrease it. Improving education levels can be provided by giving mentoring or the provision of courses. In ratoon cane, there was no effect of technical inefficiency. So an increase in ratoon cane production can be done by increasing the use of production inputs.